Adsorption behaviour of 1,3,5-trinitroperhydro-1,3,5-triazine, 2,4-dinitroanisole and 3-nitro-1,2,4-triazol-5-one on commercial activated carbons - Fawcett-Hirst, William; Temple, Tracey; Ladyman, Melissa K.; Coulon, Frederic (Elsevier, 2020)
Insensitive high explosives are increasingly being used to replace more sensitive formulations, however large quantities of environmentally hazardous wastewater are generated from loading, assembling and packing processes. Currently, there is limited literature regarding the treatment of wastewater contaminated with these hazardous insensitive high explosive materials such as 1,3,5-trinitroperhydro- 1,3,5-triazine (RDX), 2,4-dinitoranisole (DNAN) and 3-nitro-1,2,4-triazol-5-one (NTO). The preferred method of explosive wastewater treatment is adsorption by activated carbon, usually through treatment columns or fluidised beds that are simple to operate and cost effective. The aim of this research was to assess whether commercially available activated carbons would be suitable and economically viable to treat explosive wastewater containing RDX, DNAN and NTO. Bottle point tests were used to determine adsorption capacity and adsorption kinetics for the individual insensitive high explosives with three different activated carbons. Equilibrium data were fitted to the Langmuir, Freundlich and Temkin isotherms to determine the mechanisms of adsorption. Six hour bottle point tests for a mixture of the three insensitive high explosive constituents were used to consider possible preferential adsorption. As expected, RDX and DNAN were adsorbed at concentrations up to 40 mg.L-1 and 150 mg.L-1 respectively by the activated carbons tested, demonstrating the viability of treatment by adsorption. However, at the high concentrations of NTO expected in wastewater (1400 mg.L-1) activated carbons were rapidly saturated, suggesting that treatment of NTO contaminated wastewater would require prohibitively large quantities of activated carbon compared to RDX and DNAN.
Keywords: Adsorption isotherms; Adsorption kinetics; Wastewater treatment; Insensitive high explosives